Vertical Coupling Dynamic Model for Driving System with Different Suspension - WANG Xiaopeng; ZHANG Kailin; ZHANG Yu; LIU Bin (机车电传动)
The geometry structure and application category of traction motor driving system with different suspension in locomotivesystem was introduced. From the view point of actual application in engineering and based on the theory of vehicle-track couplingdynamics, the vertical dynamic model of each suspension with three rigid bodies and multi degrees of freedom which included the frameand driving system was established by way of Mass-Stiffness-Damping on the frame of B0-B0. At the same time, according to the structureof the geometry and movement relationship, the vibration differential equation of each body in each suspension was established by wayof D’Alembert principle, which provided principle base for numerical and simulation analysis for vertical vibration of driving system.Taking the nose suspension system as object, the correctness and reliability of the mathematical model was verified, and the vibrationcharacteristics of each rigid body was analyzed.